Quociente sFlt-1/PlGF como predictor de pré-eclâmpsia no segundo e terceiro trimestres de gravidez: será o uso clínico suportado pela evidência? - Vaz-de-Macedo,Carolina (2017)
Pre-eclampsia is a common and potentially serious disorder of pregnancy. An antiangiogenic state appears to be central to its development. In particular, the sFlt-1/PlGF ratio increases in pre-eclampsia, leading to its potential use as a marker for prediction and diagnosis. Immunoassays for the sFlt-1/PlGF ratio are now commercially available and can assist in the diagnosis of women with a clinical suspicion of pre-eclampsia, leading to a decrease in hospital admissions. Remarkably, information is missing on the impact of its use in pregnancy outcomes